(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Background: Every human being lives to die another day and it is imminent. However, only on a few occasions, Forensic examination of the deceased becomes a necessity in our Country. Conventional Autopsy is done in all such deaths which are reported as Medico-Legal cases. Recent scientific technologies have reached a point of advancement wherein different disciplines are interconnected to solve problems in the medical field, especially in establishing the cause of death. One such branch is Forensic Radiology, wherein the technical advances in the field of Radiology are incorporated into the field of Forensic Medicine. The branch of Forensic Medicine has made exemplary and path-breaking contributions by implementing this, especially in the western world. However, in India, it is still a dream for many Forensic Experts to explore this area. In this survey, we explore the knowledge, attitude & acceptance of Virtual Autopsy among Forensic Experts/Scientists in India.